Sociology of the change in Spain: history and transition (Foro de Educacion, 2024)
Sociology as science is relatively young, the term was coined by Comte in 1839. Since then this discipline has had a spectacular development, consoli- dating like one of most important of social sciences. The objective of this article is to present the origins and the introduction in Spain since the end of century XIX to the present time; for it we have used diverse sources that have shown us the diversity from fields to which it affects this new discipline. To describe each of them would have exce- eded the limits indicated for an article, for that reason we have shown preference for three scopes in which we took working a few years: rural sociology, sociology of the education and sociology of gender.